Diagnostic radioimmunoassay for familial amyloidotic polyneuropathy before clinical onset. - Nakazato, M (1986)
The purpose of this study is to develop an early diagnostic method for familial amyloidotic polyneuropathy (FAP) before clinical manifestations appear around the age of 30 yr. Amyloid fibrils isolated from type I FAP (FAP1) of Portuguese, Swedish, and Japanese origins consist of a variant transthyretin (TTR) that contains a methionine-for-valine substitution at position 30 or a mixture of normal TTR and this variant form. The variant TTR is present in the serum of FAP1 patients and can be measured by a radioimmunoassay (RIA) based on a nonapeptide (positions 22-30) derived from the variant TTR. Serum levels of the variant TTR in 45 Japanese FAP1 patients range from 4.71 to 17.61 mg/dl with a mean value of 9.18 mg/dl. The variant TTR is not present in the serum of 100 normal individuals, in four cases of primary and six cases of secondary amyloidosis, nor in 26 non-inheriting members of families with FAP1. The variant TTR level is measured in 24 children of 15 FAP1 patients as well. The variant TTR is already present in nine symptom-free children with the mean serum level of 11.90 mg/dl, but it is not present in 15 other children. FAP1 patients can be differentiated from non-FAP by this noninvasive diagnostic method even within families. The RIA can be applied worldwide to this intractable disorder for early diagnosis during childhood and for appropriate genetic counseling.